Reducing Organic Load From Industrial Residual Process Brine With a Novel Halophilic Mixed Culture: Scale-Up and Long-Term Piloting of an Integrated Bioprocess - Mainka, Thomas; Herwig, Christoph; Pflügl, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Integrating bioprocess solutions for treatment and subsequent reuse of saline residual process brine into industrial processes could increase the sustainability of production chains. However, such bioprocesses require large-scale and robust operation over a prolonged period. In this study, we aimed to analyze scale-up equivalence as well as continuous and stable process performance of a previously established lab scale process based on halophilic organisms for the degradation of organic contaminants (formate and aromatic compounds). To that end, a pilot-scale bubble column bioreactor system was integrated at an industrial production site. The process was successfully scaled-up and operated as a stable continuous cultivation for more than 210 days. Overall, the process proved to be robust towards changing compositions of the residual process brine stream and degradation rates for organic contaminants were close to 100%. Interestingly, due to the unsterile process conditions, the original Haloferax mediterranei culture was replaced by a novel halophilic bacterial community consisting of three bacterial genera. To further improve process economics and productivity, an optimization of the co-substrate feeding strategy for glycerol is required, as results indicated a potential correlation between glycerol feeding and formate degradation rates. To that end, decoupling of the glycerol feeding from the residual process brine feed is a potential way to increase process control options and allow for easy adaptation of the process to changing residual process brine compositions. Ultimately, the process described here could be a sustainable alternative for chemical or physical methods of treating residual process brine and once more underlines the potential to exploit natural microbial diversity for industrial purposes.